Perceived Peer Behavior and Parental Support as Correlates of Marijuana Use: The Role of Age and Gender - Goldstick, Jason E. (Subst Use Misuse, 2017)
INTRODUCTION: Parental support and perceptions of peer behavior on substance use are well-studied, but precisely how their associations vary as a function of age, and how those age-specific patterns vary by gender, remain unknown components of the developmental process underlying substance use. METHODS: Using data from an 18-year longitudinal study of predominantly African-American students at high-risk for high school dropout in Flint, Michigan (baseline average age = 14.8 years), we examined longitudinal associations between past 30-day marijuana use and three self-reported variables: perceived friend drug use, perceived friend aggression, parental support. We used varying-coefficient regression models to semiparametrically estimate how covariate effects on past 30-day marijuana use vary smoothly as a function of age; gender differences in these age-specific coefficient trajectories were also tested. RESULTS: In the unadjusted tests, the risk-enhancing effect of perceived friend drug use decreased with age in both genders, but the effect of perceived friend aggression varied only in females; in both cases, gender differences were not significant. In males, parental support had protective effects that decreased with age. The effect of both parental support differed in females, with less protective baseline effects and no evidence of age-variation. Adjusted models simultaneously including both friend and parental variables produced qualitatively similar results. CONCLUSIONS: Prevention strategies focusing on social exposures may be more effective if they are age- and gender-specific. In particular, interventions focusing on perceived peer behaviors may be more appropriate during adolescence, and those involving parental relationships may be more appropriate for males.